ANALISIS PERTIMBANGAN HUKUM HAKIM TERHADAP PUTUSAN NOMOR 92/PDT.G/2022/PN JKT.BRT TENTANG PEMBAGIAN HARTA BERSAMA - NIM. A1011211214, WAHYU SANG KRAMA WIJAYA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The division of joint property between husband and wife is an issue that often leads to disputes in the divorce process. Joint property includes all assets acquired during marriage and debts incurred by both parties during the marriage. The regulation regarding joint property and its division is governed by the Civil Code (KUHPerdata) Articles 119-126 and Law Number 1 of 1974 concerning Marriage. The research problem formulated in this study is: